Characterization of Juvenile Hormone Related Genes Regulating Cantharidin Biosynthesis in Epicauta chinensis - Ming Jiang (Nature Portfolio, 2017)
Abstract Cantharidin is a defensive toxin biosynthesized by blister beetles. It is well known for medical applications and toxicity. However, the biosynthesis process of cantharidin is still not well understood. In the present study, three genes (methyl farnesoate epoxidase (EcMFE), juvenile hormone acid O-methyltransferase (EcJHAMT) and juvenile hormone epoxide hydrolase (EcJHEH)) were identified from Epicauta chinensis. The temporal and spatial expression patterns of these three genes revealed that the expression levels of EcMFE and EcJHEH were high in the first instar larval stage of E. chinensis with EcJHEH transcripts highest in the fifth larval instar. The expression level of EcJHAMT was significantly higher in the 2nd and 3rd larval instars. The transcripts of EcMFE, EcJHEH and EcJHAMT showed a similar tendency with the cantharidin production in male blister beetles after mating. We verified the functions of these three genes in cantharidin biosynthesis using the RNA interference method. Interference of EcMFE and EcJHEH significantly inhibited the biosynthesis of cantharidin in male E. chinensis after mating, but interference of EcJHAMT has no apparent influence on cantharidin biosynthesis. We propose that EcMFE and EcJHEH may be involved in the biosynthesis of cantharidin, but JH III might not be the direct precursor of cantharidin.